+0  
 
+1
76
3
avatar

Solve the system using substitution and describe your steps:

x = y -3

2x + y = 12

 Apr 6, 2021

Best Answer 

 #1
avatar+484 
+2

Taking $x=y-3$ and plugging it into $2x+y=12$ gives $2(y-3)+y=12$, so $2y-6+y=12$, $3y=18$, $\boxed{y=6}$.

 

Now, because $x=y-3$, $x=(6)-3$, $\boxed{x=3}$

 Apr 6, 2021
 #1
avatar+484 
+2
Best Answer

Taking $x=y-3$ and plugging it into $2x+y=12$ gives $2(y-3)+y=12$, so $2y-6+y=12$, $3y=18$, $\boxed{y=6}$.

 

Now, because $x=y-3$, $x=(6)-3$, $\boxed{x=3}$

RiemannIntegralzzz Apr 6, 2021

13 Online Users

avatar